Emotional arousal and its relationship to visual perceptual speed and accuracy of defending skill of the volleyball court - Naji Hussein, Hasanain (International Journal of Psychosocial Rehabilitation, 2020)
The researcher conducted the current study in order to identify the relationship of emotional arousal, visual perceptual speed, and the accuracy of the skill of defending the court in volleyball (16) years, and the research aimed to identify emotional arousal, visual perceptual speed, and the accuracy of the skill of defending the court in volleyball and to identify the relationship of emotional arousal with visual perceptual speed and the accuracy of the skill of defending the court in volleyball. Emotional and visual perceptual speed tests and the accuracy of the preparation skill in volleyball, which are codified and applied to the Iraqi environment, and after processing the data statistically, the researcher concluded that there is a correlation between the research variables Emotional arousal, visual perceptual speed, accuracy of defending the court with volleyball, and possession players excitability emotional positive Medium which Working Action motivation in performance, and operate the condition Mental positive on me more in Speed realize variants surrounding by playing result to consciousness full performance, and that Skill Defense About basic hard which require Preparation Myself And my mind In addition to my preparation physical And the skillful in order to Investigation Best performance and defense About strikes overwhelming for the team rival.